Getting to Good Research Integrity in the Biomedical Sciences (Springer International Publishing, 2018)
This book represents the first comprehensive, gold standard reader on research integrity in the biomedical sciences. Now more than ever, the responsible conduct of research (RCR) has become critically important as new technologies affect research practices in both positive and negative ways. Since learning to do science and practicing it brings researchers into contact with a vast array of ethical issues, it is critical to know the standards and how they are evolving. Indeed, research integrity requires scientists at all levels to operate ethically in a system that supports ethical practice. This unique, foundational text covers all the relevant areas -- subject protection, research misconduct and conflict of interest as well as newly quantified concerns about research bias and non-reproducibility, as well as other unique issues. Developed by renowned experts, this compelling title discusses the full range of practices and policies that should support research that is honestly produced and disseminated. It also specifically incorporates topics noted by the National Institutes of Health as essential and required for training in RCR. Getting to Good - Research Integrity in the Biomedical Sciences is a major contribution to the literature on bioethics and will serve as an invaluable resource for all researchers, students, administrators and professionals interested in research ethics and integrity.